Views syntactic grammar for Abi Sufyan (325 A.H) In his book Altvsh language - انسام خضير خليل (College of Education for Women, 2019)
Arab heritage have teem much of the literature value, written by evacuated, who had a legacy of linguistic great scientists, but the circumstances are unknown, did not write those books or authors emerge, chose to search for a book of those compositions, he did not write to him and his book emerge, fell hands a book (Altvsh in the language) to Abu Sufyan grammar, a fourth-century scientists, as it is Abu Sufyan grammar of scientists who rolled up the time their impact, and the cryptic revelations among the stars, preferring to stand on this book and its author, a statement of the most important grammatical aspects contained therein; to notch the curtain for this world, and his book (Altvsh in strewn language and Mnzawmha and express the Koran witness so her) a title mentioned by the author on the first page of the manuscript, which shortened investigator book, Dr. Adil Hadi al-Obeidi, who branded (b Altvsh in the language), as it is this book of the most important books of Abu Sufyan, which reached us, the book launch phenomena grammatical and linguistic multi made him an important reference of linguistic references that pervaded the knowledge and science of language, was not revenue Abi Sufyan to those phenomena it is arbitrary, but rather was the result of they understand this world Galilee matters of language and arts . Were the most important reasons that led to this study:1- The lack of knowledge of the book and its author, as is this book of rare books, who has never for a recognition or the author, so I suggested that the derived importance of research of the scarcity of writers and unavailability, to be a search as evidence of this book and its author, and the source for those who wanted to know something from them. 2- The Abu Sufyan as of the fourth century scientists who did not write them prominence, Vartoat in this research highlight it; to be a new source of that century scientists who had provided the language Bnteghm scientific sober, and stand on his views grammatical, and find out their compatibility and disagreement with the views of scientists. Due to the large number of grammatical opinions contained in the book of Abu Sufyan, I thought I might be selected to study some of the views in which grammatical, as well as giving a brief biography of the author of the book.